Prevalence of depressive symptoms and related risk factors in Japanese patients with pulmonary nontuberculous mycobacteriosis. Issue 9 (21st October 2021) - Kakuta, Takeshi; Tabusadani, Mitsuru; Yamane, Kazumasa; Takao, Satoshi; Kuroyama, Yuki; Mori, Kosuke; Kawahara, Kazuma; Ono, Kazuki; Omatsu, Shunya; Senjyu, Hideaki
ABSTRACT: The objective of this study was to administer commonly used tools, the Center for Epidemiological Studies Depression Scale (CES-D) and the Hospital Anxiety and Depression Scale – Depression subscale (HADS-D), to screen for depressive symptoms in patients with nontuberculous mycobacterial pulmonary disease (NTM-PD). In addition, we sought to identify whether differences existed in the prevalence of depressive symptoms as assessed by CES-D and HADS-D, and by various predictors of depression. The presence of depressive symptoms in 95 patients with NTM-PD was assessed using the CES-D and HADS-D. Data regarding age, body mass index, pulmonary function, dyspnea, cough, and exercise capacity were obtained to examine their independent contribution as predictors of depressive symptoms. The prevalence of depressive symptoms was 37.9% based on CES-D and 26.3% based on HADS-D. The prevalence of depressive symptoms based on CES-D and HADS-D revealed significant differences between the two instruments. Analysis suggested that the presence of cough is a significant predictor of depressive symptoms as assessed by both CES-D and HADS-D. Countermeasures are necessary because some patients with NTM-PD disease have depressive symptoms. It is possible that assessment of the prevalence of depressive symptoms differs in accordance with the screening tool used.